Nasal transmissible venereal tumours in 12 dogs – a retrospective study - Ignatenko, Nataliia; Abramenko, Irina; Soto, Sara; Mueller, Ralf; Boehm, Teresa M. S. A.; Troedson, Karin; Fejos, Csilla; Hirschberger, Johannes (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2020)
Objective The aim of this study was a retrospective analysis of clinical manifestation and treatment outcome of the nasal form of transmissible venereal tumours (TVT).Material and methods Twelve dogs suffering from nasal TVT were included in this study. Patients with primary genital lesions were excluded from the study. Signalment, physical examination and laboratory findings, results of further diagnostics, and treatment results were recorded in all patients.Results The study population comprised 9 male and 4 female dogs with an (estimated) age ranging from 3 to 7 years. With one exception all dogs originated from Ukraine. Symptoms of nasal TVT included sneezing, nasal bleeding (all cases), skull infiltration (9 cases), oronasal fistulas (9 cases) and cutaneous fistulas (5 cases). Animals received vincristine sulfate at 0.7 mg/m2 i. v. weekly. The treatment course consisted of 4–9 cycles (median 5 cycles). Complete remission was achieved in all cases. All dogs were disease-free during the follow-up period (median 23.5 months, range 12–56 months). All patients tolerated the treatment very well.Clinical significance In conclusion, our data suggest that nasal TVT can have a good response to vincristine treatment. TVT should be considered as a differential diagnosis in sneezing dogs with nasal discharge or bleeding especially in young dogs and in dogs with suspected nasal tumours, even in countries without a stray animal population.
Keywords: Nasal bleeding; sneezing; oronasal fistula; cutaneous fistula